Up until today, I've always considered the following expression:
-x^2 = x^2
thinking that -x is one term, that when squared, is always positive. But in fact, I've recently discovered -x represents two terms:
-x = (minus) (1)(x)
NOT
-x = (negative x)
where x is subtracted from an assumed 0. Therefore:
-x = (0) - (1)(x)
From this theorem (is this a theorem?), then expressions such as:
-3^2 = -9 == -(3)^2 = -9
Reads as: (assumed zero) minus the square of three equals negative nine
OR
Reads as: the square of three subtracted (from an assumed zero) equals negative nine
The logical flow is: three is squared and then the opposite is found. the result is a negative nine
&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&
The above leads into an actual problem I worked on for algebra.
Determine if the point (-2, 2) passes through the line x^2 + y^2 = 4
The expression x^2 + y^2 = 4 is equivalent to the following expressions:
y^2 = -x^2 + 4
-y^2 = x^2 - 4
x^2 + y^2 - 4 = 0
The answers for each equivalent expression, plugging in point (-2, 2) are as follows (in order of expressions shown above):
x^2 + y^2 = 4
(-2)^2 + (2)^2 = 4
4 + 4 = 4
8 != 4 // this is the book's answer
y^2 = -x^2 + 4
(2)^2 = -(-2)^2 + 4
4 = -4 + 4
4 != 0
-y^2 = x^2 - 4
-(2)^2 = (-2)^2 - 4
-4 = 4 - 4
-4 != 0
x^2 + y^2 - 4 = 0
(-2)^2 + (2)^2 - 4 = 0
4 + 4 - 4 = 0
8 - 4 = 0
8 != 4 OR 4 != 0
&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&
What started all this confusion for me, was I converted x^2 + y^2 = 4 into slope-intercept form (out of habit) of y^2 = -x^2 + 4 and as shown above, my answer of 4 != 0 did not match the book's answer, which really threw me off.
It has taken me about a full day to understand and be able to define what -x^2 actually means.
0 - (1)(0 + x)^2
Anyone else encounter frustration like this? besides any frustration you may have reading reading this post or trying to understand it.